2019
DOI: 10.1016/j.scitotenv.2018.07.410
|View full text |Cite
|
Sign up to set email alerts
|

Modelling farmer choices for water security measures in the Litani river basin in Lebanon

Abstract: Lebanon is facing an increasing water supply deficit due to the increasing demand for freshwater, decreasing surface and groundwater resources and malfunctioning water governance structures. Technological and policy changes are needed to alleviate the impact of water scarcity and secure water in the future. This paper investigates farmers' preferences and willingness to pay (WTP) in a choice experiment for a series of water saving measures at plot and irrigation district level, including more timely informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…Examples included efficient irrigation technology (e.g., canal lining, drip irrigation), different crop variants, and land management practices (e.g., Falkenmark, 2013b;Chinnasamy & Agoramoorthy, 2015;Seeliger et al, 2018;Xu et al, 2019). For example, Alcon et al (2018) found that farmers in the Litani River Basin (Lebanon) were willing to pay higher water prices to support the installation of plot-level water-saving measures (e.g., irrigation scheduling, drip irrigation) and farm-scale water-metering systems for the irrigation district to increase water security and reduce uncertainty. A handful of articles indicated behavioural changes (e.g., reducing water-intensive diets) (Perrone & Hornberger, 2013) and reducing demand in competing sectors as strategies (George et al, 2010).…”
Section: Solution Pathways To Water Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Examples included efficient irrigation technology (e.g., canal lining, drip irrigation), different crop variants, and land management practices (e.g., Falkenmark, 2013b;Chinnasamy & Agoramoorthy, 2015;Seeliger et al, 2018;Xu et al, 2019). For example, Alcon et al (2018) found that farmers in the Litani River Basin (Lebanon) were willing to pay higher water prices to support the installation of plot-level water-saving measures (e.g., irrigation scheduling, drip irrigation) and farm-scale water-metering systems for the irrigation district to increase water security and reduce uncertainty. A handful of articles indicated behavioural changes (e.g., reducing water-intensive diets) (Perrone & Hornberger, 2013) and reducing demand in competing sectors as strategies (George et al, 2010).…”
Section: Solution Pathways To Water Securitymentioning
confidence: 99%
“…The different solutions were well-distributed across scales. An individual or household scale (24.2% of publications) could include strategies, such as farmers' coping responses to inadequate irrigation (e.g., Liu et al, 2008;Ferchichi et al, 2017) or agreement to pay higher fees for improved water security (e.g., Alcon et al, 2018). The community level (21.2%) could include strategies, such as local rules around water sharing (McCord et al, 2018), communal management of groundwater resources (Foster et al, 2012), or improved reliability and maintenance of water infrastructure (Borgomeo et al, 2017).…”
Section: Solution Pathways To Water Securitymentioning
confidence: 99%
“…In Colorado, canal system distributions have created for crop irrigation because irrigation canals can be valuable and aquatic habitat, especially in regions with severely degraded streams (Carlson et al, 2019). Lebanon is facing declining in canal and tube well water sources with improper water structures (Alcon et al, 2019). In southern region of Italy, a concept Grey Water Footprint (GWF) has been introduced for impact of groundwater contamination on crops.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to match the agricultural technology services with the technical needs of the farmers effectively, which is reflected in the farmers' relatively blind choice and adjustment behavior in grain production investment. Due to the differences in natural resource endowments, economic and social foundations, scale of operations, and farmers' conditions, the farmers' investment adjustment behavior varies significantly [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al [31] have found that the shortage of a labor force can be supplemented by increasing capital input. In addition, other reasons may also lead to investment adjustment behavior such as attitudes toward capital input [4], the amount of agricultural income [32], expected financial benefits from capital input [33], and differences in adjustment capabilities [34].…”
Section: Introductionmentioning
confidence: 99%